2019
DOI: 10.3390/toxins11100598
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Phytotoxic, Antimicrobial and Insecticidal Activity of the Essential Oils of Dracocephalum integrifolium

Abstract: The present investigation studied the chemical composition of the essential oils extracted from Dracocephalum integrifolium Bunge growing in three different localities in northwest China and evaluated the phytotoxic, antimicrobial and insecticidal activities of the essential oils as well as their major constituents, i.e., sabinene and eucalyptol. GC/MS analysis revealed the presence of 21–24 compounds in the essential oils, representing 94.17–97.71% of the entire oils. Monoterpenes were the most abundant subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 62 publications
4
43
1
Order By: Relevance
“…Furthermore, the HApWW samples also exhibited a higher BET surface area compared with HAp samples, and higher particle size according to TEM results. These results are in agreement with previously reported studies [55][56][57] and clearly suggest that the antimicrobial activity of the HApWW samples are a consequence of multiple factors such as their sizes, surface area, roughness, active antimicrobial substances and also the cell morphology of the tested microorganisms. The results obtained from the GC-MS analysis revealed that WW EO is mainly constituted of monoterpenes.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the HApWW samples also exhibited a higher BET surface area compared with HAp samples, and higher particle size according to TEM results. These results are in agreement with previously reported studies [55][56][57] and clearly suggest that the antimicrobial activity of the HApWW samples are a consequence of multiple factors such as their sizes, surface area, roughness, active antimicrobial substances and also the cell morphology of the tested microorganisms. The results obtained from the GC-MS analysis revealed that WW EO is mainly constituted of monoterpenes.…”
Section: Resultssupporting
confidence: 93%
“…Considering their properties and their chemical structure, one of the proposed mechanism in the forming of HApWW samples would be through hydrogen bonding and/or dipole interactions. Furthermore, the antimicrobial activity presented by the WW and HApWW samples is strongly correlated with the presence of the major constituents α-Fenchene, Sabinene, β-Thujene, β-myrcene and methyl salicylate, which were reported to possess good antimicrobial activity against microbial strains such as E. coli, B. subtillis, P. aeruginosa, S. cerevisiae and C. albicans [57]. Moreover, the studies reported by Ghaffari et al [58] regarding EOs having most abundant chemical constituents β-pinene, β-myrcene, limonene, and caryophyllene also demonstrated antimicrobial activity against some highly susceptible strains such as E. coli, C. albicans, and S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…At the minimum inhibitory concentration (MIC) [0.8% (v/v)], 1,8-cineole showed bactericidal effect on planktonic E. coli cells, with membrane disruption as the bactericidal mechanism identified. Other authors reported MICs of 1,8-cineole for E. coli strains � 0.8% (v/v) [13][14][15]. Nevertheless, the effect of this phytochemical on E. coli biofilms has not been extensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal activity of sabinene 29 and limonene 30 against Saccharomyces cerevisiae, Candida spp., Cryptococcus neoformans, and Malassezia furfur has been reported. Deena and Thoppil 31 investigated the antibacterial activity of the essential oil from L. camara collected in Calicut, India.…”
Section: Resultsmentioning
confidence: 99%